2014
DOI: 10.1186/scrt499
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning of bone marrow mesenchymal stem cells by prolyl hydroxylase inhibition enhances cell survival and angiogenesis in vitro and after transplantation into the ischemic heart of rats

Abstract: IntroductionPoor cell survival and limited functional benefits have restricted the efficacy of bone marrow mesenchymal stem cells (BMSCs) in the treatment of myocardial infarction. We showed recently that hypoxia preconditioning of BMSCs and neural progenitor cells before transplantation can enhance the survival and therapeutic properties of these cells in the ischemic brain and heart. The present investigation explores a novel strategy of preconditioning BMSCs using the Hypoxia-inducible factor 1α (HIF-α) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 50 publications
3
81
0
Order By: Relevance
“…Dimethyloxalylglycine (DMOG) is a prolyl hydroxylase inhibitor that permits HIF1a pathway signaling, leading to upregulation of survival genes and growth factors [111]. Liu et al reported that exposure of BM-MSCs to DMOG mimicked the effects of hypoxia preconditioning by enhancing the secretion of proteins and increasing cell survival in vitro [121]. Once transplanted into myocardially infarcted rats, DMOG-preconditioned BM-MSCs showed less apoptosis, smaller infarct size, and enhanced cardiac function, suggesting that pretreatment with DMOG or other prolyl hydroxylase inhibitors may be a valuable therapeutic approach to mimic hypoxic preconditioning.…”
Section: Preconditioning Of Stem Cells To Enhance Stem Cell Efficacymentioning
confidence: 98%
“…Dimethyloxalylglycine (DMOG) is a prolyl hydroxylase inhibitor that permits HIF1a pathway signaling, leading to upregulation of survival genes and growth factors [111]. Liu et al reported that exposure of BM-MSCs to DMOG mimicked the effects of hypoxia preconditioning by enhancing the secretion of proteins and increasing cell survival in vitro [121]. Once transplanted into myocardially infarcted rats, DMOG-preconditioned BM-MSCs showed less apoptosis, smaller infarct size, and enhanced cardiac function, suggesting that pretreatment with DMOG or other prolyl hydroxylase inhibitors may be a valuable therapeutic approach to mimic hypoxic preconditioning.…”
Section: Preconditioning Of Stem Cells To Enhance Stem Cell Efficacymentioning
confidence: 98%
“…Cell refinement can be achieved, for instance, by density centrifugation [13], magnetic-(MACS) [26,33] or fluorescence-activated cell sorting (FACS) [99] or by pre-in vitro priming [8,13,27,33,58,99,100]. Density centrifugation is often used to isolate mononuclear cells (BMMNC) from BM cell suspension [13,75], while MACS and FACS achieve a higher degree of selectivity by picking up cells according to their surface markers (cluster of differentiation, CD).…”
Section: Cell Choice Refinement Dosage and Timing Of Administrationmentioning
confidence: 99%
“…Density centrifugation is often used to isolate mononuclear cells (BMMNC) from BM cell suspension [13,75], while MACS and FACS achieve a higher degree of selectivity by picking up cells according to their surface markers (cluster of differentiation, CD). MACS and FACS can also be used to achieve sub-populations by negative selection, whereby cells are labeled and discarded according to the expression of markers which are not of interest for a particular experiment [33,99]. Finally, in vitro preconditioning is used to obtain sub-populations endowed to survive in the harsh conditions of the myocardium.…”
Section: Cell Choice Refinement Dosage and Timing Of Administrationmentioning
confidence: 99%
See 2 more Smart Citations